Film England culturally English filmmaking since the 1990s - Higson, Andrew (I. B. Tauris, 2011)
Andrew Higson demonstrates how a variety of Englishnesses have appeared on screen since 1990m, and surveys the genres and production modes that have captured those representations. He examines several contemporary 'English' dramas that embody the transnationalism of contemporary cinema, from 'Notting Hill' to 'The Constant Gardener'.